Bibliometric insights into the intellectual dynamics of forensic accounting research - Rana Mustafa Airout; Sadam Abu Azam; Mohammad Airout (Cogent Business & Management, 2024)
This study comprehensively evaluates 268 articles on forensic accounting using a meta-literature approach. By integrating quantitative and qualitative analysis, the research identifies prominent authors, publications, and themes. The analysis reveals four key areas of focus: the fraud triangle and financial statement fraud, corporate governance's role in fraud prevention, fraud detection techniques, and the broader impacts of fraud. Furthermore, the review highlights 58 potential areas for future research, aiding scholars in identifying critical gaps in the field of forensic accounting.
Keywords: 650; Forensic; accounting; fraud triangle; fraud detection; fraud prevention; bibliometrics